FEATURES OF THE QUALITY ASSURANCE SYSTEM OF VOCATIONAL EDUCATION AND TRAINING IN BELGIUM (Innovative professional education, 2025)
The article discussed the quality assurance system of vocational education in French-speaking Belgium, focusing on the French Qualifications Framework. It analyzes the implementation of the competence-based approach and certification based on learning outcomes, as well as the role of various institutions in ensuring the quality of education. Based on the Belgian experience, the article highlights the key features of improving the system of quality assurance in vocational education and training and the assessment of competencies acquired in the process.
Keywords: French-speaking Belgium, vocational education, French-speaking Qualifications Framework, European standard quality assurance system, competence-based approach, competence assessment, professional development of educators, quality of education